The “Excluded Area” Policy in the Naga Hills: Colonial Administration and Its Impact on Naga Society - Bideno R Ezung (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The “Excluded Area” policy introduced by the British colonial government in India played a major role in shaping the political, social, and cultural development of the Naga Hills. Implemented under the Government of India Act 1935, the policy separated certain tribal regions from direct provincial administration. The British justified this decision by claiming that tribal societies required protection from outside influence and exploitation. However, the policy also helped the colonial government maintain strategic control over frontier regions while limiting political participation by local communities. In the Naga Hills, the Excluded Area system preserved many traditional customs and institutions but also isolated the region from mainstream political developments in British India. This article examines the origins, objectives, implementation, and long-term impact of the Excluded Area policy in the Naga Hills and explains how it contributed to the rise of Naga political consciousness and identity.